Depression and anxiety symptoms during the transition to early adulthood for people with intellectual disabilities. Issue 5 (23rd February 2018) - Austin, K. L.; Hunter, M.; Gallagher, E.; Campbell, L. E.
Abstract: Background: The transition to adulthood is a major developmental milestone; a time of self‐discovery and increased independence. For young adults (YA) with intellectual disabilities (ID), however, this period is especially challenging. The increased incidence of mental health disorders in this population, such as depression and anxiety, make this transition even more difficult, increasing caregiver burden at a time when the young adult would traditionally be gaining independence. It is not clear, however, why YA with ID are more susceptible and what factors may predict mental health symptoms. Method: Potential risk and protective factors (demographic variables, coping styles, sense of hopelessness, unmet achievement of adulthood milestones, self‐reflection and insight) of anxiety and depression symptoms were assessed in 55 YA with ID and a sample of age‐matched controls. Results: Insight was the strongest predictor of anxiety (with gender in the controls) for YA with and without ID, with increased insight predicting fewer anxiety symptoms. However, YA with ID had significantly less insight than their aged‐matched counterparts and significantly higher levels of anxiety. They were also less likely to have achieved traditional adulthood milestones. Maladaptive coping was the strongest predictor of depression for YA with ID. In comparison, both maladaptive coping and insight predicted depression in controls. More maladaptive coping predicted increased depressive symptoms in both populations, whilst increased insight predicted fewer depressive symptoms in controls. Conclusions: Insight and maladaptive coping are potential targets in the treatment of anxiety and depression among YA with ID. Longitudinal intervention studies exploring the efficacy of such targeted programmes in reducing mental health symptoms and improving the transition to adulthood for these young people are recommended.